The research environment. - Jawan, Jayum; Ariff, Arbakariya (Universiti Putra Malaysia Press, 2012)
Chapter discusses the research facilities and opportunities available to postgraduate students and their supervisors and what are usually available, including funds that may be availble to support postgraduate students.